Stratifikasi Sosial dalam Perspektif Al-Qurâan - Sarbini, Ahmad (Jurnal Ilmu Dakwah, 2008)
The Holy Book (Al-Qurâan) can be made as directive in ekplanating human being character. Al-Qurâan constitute representation of soul of human being and can bge made directive (al-huda), parter (al-furqon) and solution (as-Syifa). One of itâs approach is with seeing characteristic simbologi Al-Qurâan. It can be reference to explanate human being character.